Multifunctional Roles of the Actin-Binding Protein Flightless I in Inflammation, Cancer and Wound Healing - Strudwick, Xanthe L.; Cowin, Allison J. (Frontiers in Cell and Developmental Biology, 2020)
Flightless I is an actin-binding member of the gelsolin family of actin-remodelling proteins which inhibits actin polymerization but does not possess actin severing ability. Flightless I functions as a regulator of many cellular processes including proliferation, differentiation, apoptosis, and migration all of which are important for many physiological processes including wound repair, cancer progression and inflammation. More than simply facilitating cytoskeletal rearrangements, Flightless I has other important roles in the regulation of gene transcription within the nucleus where it interacts with nuclear hormone receptors to modulate cellular activities. In conjunction with key binding partners Leucine rich repeat in the Flightless I interaction proteins (LRRFIP)1/2, Flightless I acts both synergistically and competitively to regulate a wide range of cellular signalling including interacting with two of the most important inflammatory pathways, the NLRP3 inflammasome and the MyD88-TLR4 pathways. In this review we outline the current knowledge about this important cytoskeletal protein and describe its many functions across a range of health conditions and pathologies. We provide perspectives for future development of Flightless I as a potential target for clinical translation and insights into potential therapeutic approaches to manipulate Flightless I functions.